Conceptions et usages de l'exemple dans l'enseignement de l'histoire à l'université. Foisonnement, tensions, décalages et paradoxes - Anne Emmanuelle Demartini (Nantes Université, 2016)
What is an example to academic teachers in history and what for? What value is placed on the example and how is it used in teaching history at the University? What relationship between uses of example and nature of history? How the two modalities of example (exemplum and casus) are used in teaching? Based on 8 interviews, the paper explores the proliferation of pratices, uses, functions of examples and questions the epistemological basis of the practices. The value placed on the example that has a function both pedagogical and cognitive is related to an implicit epistemology. But since case in research field is considered as the opposite of example, it becomes the same in the teaching of history.